Modeling of terahertz radiation absorption temperature distribution in biological tissue of a cattle using Simulink-MATLAB model - Kurnia, Dewi; Hamdi, Muhammad; Muhammad, Juandi; Saktioto, Saktioto; Yupapin, Preecha; Abdullah, Hewa Yaseen (Lembaga Studi Pendidikan and Rekayasa Alam Riau, 2021)
Terahertz radiation (THz) has interesting and effective properties in the field of biomedical imaging techniques, this is because of its ability to interact easily, is not ionized, and does not damage biological tissue. The purpose of this study was to determine the effect of THz radiation power density on temperature distribution and heat production in bovine biological tissue consisting of skin, fat, and muscle using a modeling approach. This study uses biophysical computation techniques with the Simulink-MATLAB model in the 0.1 – 1 THz frequency range, 50 – 150 mW power, and 5 – 25 mW/mm3 power density. Temperature distribution modeling is carried out in two ways, namely with different power densities and variations in the circumference of the THz radiation source. The results showed that the higher the power density used, the greater the absorbed radiation energy with increasing temperature. This causes the temperature distribution in the biological tissue to be wider and the production of heat in the tissue will increase. The results of imaging analysis of temperature distribution to depth in bovine biological tissue, show that fat tissue has less heat production compared to other tissues. The comparison of experimental data and modeling results shows an error percentage of 1.09%.